Pengaruh Kontrol Diri dan Gaya Hidup Hedonis terhadap Perilaku Konsumtif pada Dewasa Awal di Kabupaten Karawang - Asrori Pradana; Nuram Mubina; R Yuwono Pratomo (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the effect of self-control and hedonistic lifestyle on consumptive behavior among young adults in Karawang Regency. The research method used a quantitative approach with a causality design. The research sample consisted of 358 young adult participants determined using convenience sampling. The instruments used included the Indonesian version of the self-control scale by Arifin and Milla (2020), a hedonistic lifestyle scale developed by the researchers based on the aspects of hedonistic lifestyle by Wells and Tigert, and a consumptive behavior scale developed by the researchers based on the indicators of consumptive behavior by Sumartono, which had been tested for validity and reliability. Data analysis used multiple regression tests with the help of SPSS 25. The results showed that self-control and hedonistic lifestyle simultaneously had a significant effect (significance value = 0.000) on consumptive behavior (R² = 0.736). Partially, self-control had a negative effect on consumptive behavior, while hedonistic lifestyle had a positive effect. These findings confirm that consumptive behavior in early adulthood can be suppressed through increased self-control, but hedonistic tendencies actually reinforce consumptive behavior. This study contributes to the development of psychology, particularly in understanding the factors that influence consumptive behavior in early adulthood.